SENSITIVITY ANALYSIS IN FLEXIBLE PAVEMENT PERFORMANCE USING MECHANISTIC EMPIRICAL METHOD (CASE STUDY: CIREBON–LOSARI ROAD SEGMENT, WEST JAVA) - E. Samad (Journal of the Civil Engineering Forum, 2011)
Cirebon – Losari flexible pavement which is located on the North Coast of Java, Indonesia, is in the severe damage condition caused by overloading vehicles passing the road. The need for developing improved pavement design and analysis methods is very necessary. The increment of loads and quality of material properties can be evaluated through Mechanistic-Empirical (M-E) method. M-E software like KENLAYER has been developed to facilitate the transition from empirical to mechanistic design methods. From the KENLAYER analysis, it can be concluded that the effect of overloading to the pavement structure performance is difficult to minimize even though the first two layers have relatively high modulus of elasticity. The occurrence of 150%, 200%, and 250% overloading have a very significant effect in reducing 84%, 95%, and 98% of the pavement design life, respectively. For the purpose of increasing the pavement service life, it is more effective to manage the allowable load.